ANALYSIS ON RUNNING DICTATION TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT - Ridwan Fadhli; Eusabinus Bunau; Wardah Wardah (Universitas Tanjungpura, 2022)
AbstractThis research is mainly intended to find out the effectiveness of Running DictationTechnique. In line with the objectives of the research, the researcher used comparativemethod with quantitative approach. In collecting the data, the researcher useddocumentation in form of secondary data. From previous research the researcher has read,the researcher aims to outline the results of 3 research articles subject, and then combinethem to build up a conclusion. They are from: (1) Mentari, Ade (2018), (2) Riyanti, EkaWidi (2017), (3) Aini, Aldilla Arin (2015). The population in this research were: (1) Studentof Class VIII 3 MTs Amin Darussalam, (2) Student of Class VIII A MTs N Susukan, (3)Students of Class X Social 1 SMAN 1 Bawang Banjarnegara. The analysis used DescriptiveAnalysis, Paired Samples T-Test, Normality Test, and Hypothetical Test. The resultsshowed that there were a significant improvement in writing skills by using runningdictation technique and there was a difference in value between three different subjects inapplying running dictation technique to improve students’ writing skills in descriptive text.From the data collected, the running dictation technique was proven effective since thethree-research subject showed improvement on writing skills in descriptive text by usingrunning dictation technique.Keywords: Running Dictation Technique, Writing Skills, Descriptive Text